2011
DOI: 10.1063/1.3589982
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the two-dimensional electronic spectra of the Fenna-Matthews-Olson complex using the hierarchical equations of motion method

Abstract: We apply the Liouville space hierarchical equations of motion method to calculate the linear and two-dimensional (2D) electronic spectra of the Fenna-Matthews-Olson (FMO) protein complex from Chlorobium tepidum, using a widely used model Hamiltonian. The absorption and linear dichroism spectra of the FMO complex, as well as the main features of the 2D spectra are well reproduced. However, comparison with the recent experimental 2D spectra reveals several limitations of the current model: (1) The homogeneous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
147
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(152 citation statements)
references
References 67 publications
4
147
0
Order By: Relevance
“…Fig. 5 shows a close up of spectral densities discussed in the main text, and in additions includes for convenient reference the single-peak Drude-Lorentz density (dotted line, J DL ), used in some previous studies [17][18][19]. …”
Section: Appendixmentioning
confidence: 99%
See 3 more Smart Citations
“…Fig. 5 shows a close up of spectral densities discussed in the main text, and in additions includes for convenient reference the single-peak Drude-Lorentz density (dotted line, J DL ), used in some previous studies [17][18][19]. …”
Section: Appendixmentioning
confidence: 99%
“…While a sluggish bath relaxation leads to prolonged population beatings in the FMO network, calculations of 2d echo-spectra show oscillations of the exciton cross-peaks for only about 1/6th of the experimentally recorded time at T = 150 K [18]. For an even longer bath-relaxation cross-peak oscillations are absent already at T = 77 K [19]. Hence the search continues for theoretical models which support a long-lasting coherent dynamics leading to cross-peak oscillations in 2d echo-spectra and simultaneously retain the fast dissipation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…By generalizing hierarchy structures, one can deal with a low temperature system 45,59,60 as well as general spectral distributions 61 including Brownian spectral distributions [62][63][64][65] and a Lorentzian distribution. 66,67 This formalism is valuable since it can handle not only strong system-bath coupling, but also quantum coherence between the system and bath, which plays important roles in multidimensional spectroscopy, [50][51][52][53][54][55][67][68][69] energy transfer processes in photosynthetic antenna systems [70][71][72][73][74][75][76][77] and DNA systems, 78 ET process, 49,79 and processes discussed in a quantum information theory. [80][81][82][83] While most research with the HEOM approach assumed the Drude spectral distribution, we have shown that the ET problem can be handled in a nonperturbative manner for both the system-bath and ET couplings by applying the hierarchy formalism to the Brownian oscillator (BO) spectral distribution that arises from the canonical transformation of ET system.…”
Section: Introductionmentioning
confidence: 99%